A review of recent advances in vibro-acoustic system response variance determination in statistical energy analysis: A tribute to Preston Smith, Jr - Koch, Robert M. (The Journal of the Acoustical Society of America, 2012)
Since the pioneering work of Preston Smith, Jr. and Richard Lyon in 1959 in the development of the theory of Statistical Energy Analysis (SEA), followed by many others in the 1960’s on through today, the US Navy has utilized the important SEA vibro-acoustic simulation approach for high frequency self- and radiated-noise predictions of a multitude of undersea vehicles and systems. As a tribute to Preston Smith, this talk will review the current state of research in the determination of the variance/probability distribution about the mean response of a system modeled in SEA. While the subject of system response variance (or confidence interval) has obviously been of interest since the inception of this energy-based statistical method, there has been significant recent research in the literature advancing this area that is worth reviewing. As an additional acknowledgement of Preston Smith’s later important work in the area of underwater cylindrical shell acoustics, the current presentation will also revisit the canonical structural acoustic problem of a point-excited, finite cylindrical shell with fluid loading and compare SEA-derived radiated noise level predictions with a variety of different classical analytical and modern day numerical approach solutions (e.g., FEA, EFEA/EBEA, closed form plate and shell theory solutions).